IDENTIFIKASI JENIS MAKRO FAUNA TANAH DI BAWAH TEGAKAN AREN (Arenga pinnata Merr.) DI KECAMATAN SUNGAI RAYA HULU SUNGAI SELATAN - Nurhida Anggi Nirmala; Dina Naemah; Susilawati Susilawati (Universitas Lambung Mangkurat, 2024)
This study aims to identify the type of soil macrofauna under the palm stand, Calculate the relative density value, relative frequency and important value index of soil macrofauna under the palm stand. The data collected on each observation plot by taking samples of soil macrofauna contained in the soil in the macrofauna research and analysis plots include density, relatif density, frequency, relative frequency, and diversity index. The results of the identification and calculation of soil macrofauna are arranged in several tables that will be calculated for the density of the fauna. Based on observations, 16 types of macrofauna were obtained that belonged to 11 families. Analysis of macrofauna calculations that have been carried out at the site found as many as 16 types of macrofauna dominated by termite types (Coptotermes curvignatus) with a total of 155 types contained in 10 number of measurement plots. Based on the results of the shannon wiener index of 1.220, soil macrofauna under the palm stand are included in the medium category.Penelitian bertujuan untuk mengidentifikasi jenis makrofauna tanah yang terdapat di bawah tegakan aren,menghitung nilai kerapatan relatif, frekuensi relatif, dan Indeks Nilai Penting (INP) makrofauna tanah di bawah tegakan aren. Data dikumpulkan di setiap plot pengamatan dengan mengambil sampel makrofauna tanah yang terkandung dalam tanah dalam plot penelitian dan analisis makrofauna meliputi densitas, frekuensi, frekuensi relatif, dan indeks keanekaragaman. Hasil identifikasi dan perhitungan makrofauna tanah disusun dalam beberapa tabel yang akan dihitung untuk kepadatan fauna. Berdasarkan pengamatan, diperoleh 16 jenis makrofauna (11 famili ditemukan). Ditemukan 16 jenis makrofauna yang didominasi oleh jenis rayap (Coptotermes curvignatus) dengan total 155 jenis pada 10 jumlah plot pengukuran. Indeks Shannon wiener sebesar 1,220, makrofauna tanah di bawah tegakan aren masuk dalam kategori medium.